2022
DOI: 10.3390/nu14122382
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal Bisphenol a Exposure and Postnatal Trans Fat Diet Alter Small Intestinal Morphology and Its Global DNA Methylation in Male Sprague-Dawley Rats, Leading to Obesity Development

Abstract: In this study, we aimed to determine whether a postnatal trans fat diet (TFD) could aggravate prenatal bisphenol A (BPA) exposure effects on offspring’s small intestine and adulthood obesity, due to the relatively sparse findings on how the interaction between these two variables interrupt the small intestinal cells. Twelve pregnant rats were administered with either unspiked drinking water (control; CTL) or BPA-spiked drinking water throughout pregnancy. Twelve weaned pups from each pregnancy group were then … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 70 publications
0
1
1
Order By: Relevance
“…This could also explain the diminished downstream pathways of FA/lipid and nucleotide/nucleoside biosynthesis in the TFD groups compared to the ND groups ( Fig 8 ). Unfortunately, the decrease in the nucleotide/nucleoside biosynthesis pathway in TFD offspring relative to ND offspring in the present study was not evident in their small intestinal global DNA methylation as reported in our previous study [ 79 ]. It is possible that dysregulated nucleotide/nucleoside biosynthesis occurred elsewhere, such as in the liver, where de novo purine nucleotide synthesis takes place.…”
Section: Discussioncontrasting
confidence: 68%
“…This could also explain the diminished downstream pathways of FA/lipid and nucleotide/nucleoside biosynthesis in the TFD groups compared to the ND groups ( Fig 8 ). Unfortunately, the decrease in the nucleotide/nucleoside biosynthesis pathway in TFD offspring relative to ND offspring in the present study was not evident in their small intestinal global DNA methylation as reported in our previous study [ 79 ]. It is possible that dysregulated nucleotide/nucleoside biosynthesis occurred elsewhere, such as in the liver, where de novo purine nucleotide synthesis takes place.…”
Section: Discussioncontrasting
confidence: 68%
“…For example, Wang et al [50] reported that elevated prenatal mercury exposure was associated with a higher risk of childhood obesity, and such risk was reduced by adequate folate ingestion. Zulkifli et al [51] found that prenatal bisphenol A exposure significantly affected a rat's offspring's physiological parameters and intestinal function, and that there might be compensatory responses to postnatal trans-fat diets in the combined bisphenol A group. Another animal trial conducted using a swine model indicated that the propensity for obesity of pig fetuses exposed to prenatal malnutrition might be moderated by controlled food intake [52].…”
Section: Discussionmentioning
confidence: 99%